The Philippines and Japan in America's shadow - Fujiwara, Kiichi; Nagano, Yoshiko (NUS Press, 2011)
Japan and the Philippines both spent part of the 20th century under American rule, and the experience left an indelible imprint on both societies. Conventional wisdom suggests that American rule in the Philippines, while clearly a form of colonialism, was mitigated by American reluctance to be a colonial power and by early steps to transfer government functions to Filipinos. Similarly, the American occupation of Japan is understood to represent a necessary transitional phase between autocracy and democracy.